Evidence of Reverse Brain Drain in Selected Asian Countries: Human Resource Management Lessons for Malaysia - Ismail, Maimunah; Kunasegaran, Mageswari; Rasdi, Roziah Mohd (Organizations and Markets in Emerging Economies, 2014)
Reverse brain drain (RBD) is a fertile area to examine in the inter-countries movement of professionals. The basic idea of RBD is that the professionals who migrated to the industrialized nations represent potential human resources for the socioeconomic development of their home countries. It is argued that every ‘brain drain’ is a potential ‘brain gain’ for a country. However, there is inconclusive evidence on the best practices of RBD that may become lessons for any country to adopt in tapping the valuable experiences of the intellectual elites. Using ‘human capital theory’ and ’diffusion of innovation theory’, this conceptual paper specifically aims i) to illustrate evidence of the best practices of RBD in selected Asian developing countries of South Korea, Taiwan, China, and India that have commended track records in dealing with RBD; and ii) to suggest strategies for Malaysia, which is a beginner in developing the RBD programs, to adopt the best practices as experienced by the selected countries.
Keywords: brain drain; reverse brain drain; adoption of innovation; human resource management; developing countries